2016
DOI: 10.1371/journal.pone.0146615
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of Patients on Health-Care for Co-Morbid Diabetes and Chronic Kidney Disease: A Qualitative Study

Abstract: BackgroundMulti-morbidity due to diabetes and chronic kidney disease (CKD) remains challenging for current health-systems, which focus on single diseases. As a first step toward health-care improvement, we explored the perspectives of patients and their carers on factors influencing the health-care of those with co-morbid diabetes and CKD.MethodsIn this qualitative study participants with co-morbid diabetes and CKD were purposively recruited using maximal variation sampling from 4 major tertiary health-service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(108 citation statements)
references
References 35 publications
2
102
0
4
Order By: Relevance
“…One of the key findings from this study was that there is a long lasting emotional impact that results from receiving renal diet advice, and an ongoing emotional burden associated with applying this advice. Similar to previous research (White & Grenyer 1999;Low et al 2014;Lo et al 2016;Morris et al 2017), patients felt poorly equipped to deal with the challenges and complexity of dietary changes required. Interestingly, the emotional experience of carers was similar to that of patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…One of the key findings from this study was that there is a long lasting emotional impact that results from receiving renal diet advice, and an ongoing emotional burden associated with applying this advice. Similar to previous research (White & Grenyer 1999;Low et al 2014;Lo et al 2016;Morris et al 2017), patients felt poorly equipped to deal with the challenges and complexity of dietary changes required. Interestingly, the emotional experience of carers was similar to that of patients.…”
Section: Discussionsupporting
confidence: 53%
“…; Lo et al . ; Morris et al . ), patients felt poorly equipped to deal with the challenges and complexity of dietary changes required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Data Availability Statement for their qualitative study recently published in PLOS Medicine , Christopoulos et al (2015) stated, “Public availability of data could potentially compromise participant privacy. Participants did not consent to have their full transcripts or excerpts of transcripts made publically [ sic ] available.” Qualitative studies published in PLOS One subsequent to the PLOS policy adoption have made similar claims (Natoli et al, 2015; Tang et al, 2015) (although there have also been notable, and welcome, exceptions (Lo et al, 2016)).…”
Section: Data Sharing In Qualitative Researchmentioning
confidence: 81%
“…Twelve focus groups were conducted with 58 patients, with a further six focus group performed with 35 tertiary health professionals and four focus groups with 22 GPs. Semi‐structured interviews were conducted with eight care‐givers and eight heads of specialist units A quantitative study of GPs evaluating the commonest reported health‐service barriers to health‐care.…”
Section: Co‐designing An Evidence‐based Model Of Care For Patients Wimentioning
confidence: 99%
“…The detailed methodology and results of these qualitative and quantitative studies have been previously published …”
Section: Co‐designing An Evidence‐based Model Of Care For Patients Wimentioning
confidence: 99%